Simulación de un convertidor DC/DC cuadrático elevador con control modo corriente mediante Matlab/Simulink - Carlos Andrés Peñaloza-Luna; German Enrique Gallego-Rodríguez; Jhon Jairo Ramírez-Mateus; Karla Cecilia Puerto-López; Karla Yohana Sánchez-Mojica (Mundo Fesc)
This article presents the design and simulation of a cascade quadratic boost converter with a single active switch, whose output voltage is controlled by average current mode, for a nominal output power of 200W and a voltage of 180Vdc. The main application of this converter is the regulation of output voltage with loads that require high DC voltage levels and, due to their characteristics, demand an N number of stages with the highest voltage gain and nominal power. Simulation results for different converter configurations with linear and nonlinear loads exhibiting voltage harmonics were obtained using Matlab/Simulink. A classic PI controller has been proposed for the voltage regulator, which achieves good performance as a regulator. Finally, the operation of the quadratic boost converter using multiple power levels and adjustable output voltages is analyzed.